The first clinical experience of using bone chips to promote sternum reossification after median sternotomy - M. S. Kuznetsov; V. V. Shipulin; E. V. Lelik; G. G. Nasrashvili; D. S. Panfilov; B. N. Kozlov (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to evaluate the first experience of using bone chips in sternum metallic osteosynthesis in terms of safety and clinical efficacy.METHODS AND MATERIALS. 20 patients, 10 people in each group (11 men and 9 women; the average age in Group 1 was 74.2±5.3 years; in Group 2 – (72.4±6.7) years) were enrolled in the study. In accordance with the objective of the study, when suturing the sternum, bone-chip grafts were inserted into the spongy substance in Group 1 patients. Group 2 included patients who underwent surgical treatment according to the generally accepted standard protocol: bone wax was applied to the spongy bone tissue of the sternum.RESULTS. The evaluation of sternum reossification was performed with spiral computed tomography. The initial state of the bone tissue was examined before the operation, in the early postoperative period (12 days) and in the midterm period – 12 months after the operation. The results were evaluated on a point scale: 0 points – sternal diastasis more than 3 mm, 12 points – complete sternal consolidation. In the early postoperative period, the degree of sternum fusion did not differ in both groups. (Group 1 – (3.5±0.7); Group 2 – (3.5±0.8) points). In the mid-term follow-up (12 months after), the degree of sternum fusion in patients of Group 1 was (11±0.7) points, which was almost two times higher than in patients of Group 2 – (5.6±3) points.CONCLUSION. The use of Xeno-materials for bone grafting in patients at high risk of impaired reossification after median sternotomy is safe and effective.